Manejo de plagas en yuca - Bellotti, Anthony C.; Reyes Q., Jesús Antonio; Arias V., Bernardo; Vargas H., Octavio (International Center for Tropical Agriculture, 1979)
Aspects related to pest management in cassava are discussed: (1) favorable factors involved insect/plant/environment interactions; (2) characteristics of insect survival; (3) integrated, biological control and pest management. On the basis of research conducted by CIAT on Erinnyis ello, a management program is proposed which incorporates different techniques such as biological control [natural enemies of eggs (Trichogramma spp., Telenomus spp.), larvae (Polistes spp., Podisus sp., Apanteles sp., Drino sp., Belsovia sp. and Chetogena sp.) and pathogens (Bacillus spp. and the nuclear granulosis virus)], light traps and manual collection of larvae. The habits, order and family of parasites, predators and pathogens of E. ello are given in table form. (CIAT)